Kelimpahan Gastropoda pada Habitat Lamun Berbeda di Pulau Bone Batang Sulawesi Selatan - Dody Priosambodo (Jurnal Ilmu Kelautan SPERMONDE, 2016)
Research about gastropods abundance on different types of seagrass habitat has been done in Bone Batang Island, South Sulawesi. The aim of this research was to compared the gastropods abundance on three different types of seagrass habitat: intertidal seagrass meadow, subtidal seagrass meadow and reef flat seagrass meadow. Research were also conducted to investigated the correlation between number of seagrass shoots and the abundance of gastropods on specific determined area. Data collected from eight stations consist of: five stations on intertidal seagrass meadow, two stations on subtidal seagrass meadow and one station on reef flat seagrass meadow. Every station were also consist of control that placed on bare sediment area where seagrass shoots were absent. Seagrass shoots density were counted using sediment PVC corer with 0.157 m in diameter and 0.25 m height. Gastropod samples were collected using tarp method with 4 x 3 m brown plastic tarp. Correlation between number of seagrass shoots and the abundance of gastropods were analyze using Pearson Product Moment Correlation Analysis. Result showed that the number of gastropods species and abundance varied among stations with the number tend to be higher on control site in most type of habitat. Correlation analysis showed there is no correlation between the number of seagrass species/shoot density with the number of gastropod species/abundance on each type of seagrass meadow habitat. It can be concluded that the presence of gastropods in most type of seagrass meadow habitat is not depend on seagrass number of species and seagrass shoots density.